Grain quality of milled rice in various supermarkets in Damariñas City, Cavite - Tuano, A. P. P. (Journal of Human Ecology, 2020)
All open-bin milled rices (n = 44) sold in selected supermarkets along Emilio Aguinaldo Highway in Dasmariñas City, Cavite were collected in July-August 2017 and subjected to grain quality analysis, specifically those affecting rice cooking and eating quality. Rice with intermediate apparent amylose content (AC) (mean AC 21.4%) predominated this sample set, followed by high AC. Alkali spreading value (ASV) showed 21 out of 44 samples to have intermediate gelatinization temperature (GT) with mean ASV of 4.5. AC-GT combinations showed that supermarket milled rices in Dasmariñas, Cavite were predominantly of the intermediate AC-intermediate GT type which have soft texture when cooked. This was followed by high AC-intermediate GT type which have medium texture. Gel consistency (GC) test showed that most of the high-AC samples were hard on cooling but the overall mean GC of 58 mm corresponded to medium GC. Optimum cooking time (OCT) was found to be around 17-19 min. Market price was found negatively correlated with AC and OCT while ASV and price had a highly positive correlation. OCT was significantly positively correlated with AC but was negatively correlated with ASV. Determining the grain quality of market rice samples in supermarkets or public markets is of significance especially in market milled rice grading and clustering relative to rice end-use quality and price. Results of this study serve as baseline data on Philippine market milled rice quality. The survey started in 2012 at PhilRice Los Baños and was geared towards helping Filipino consumers and inspectors recognize common rice quality types in the local market.